Efektivitas Formulasi Spora Bacillus subtilis B12 sebagai Agen Pengendali Hayati Penyakit Hawar Daun Bakteri pada Tanaman Padi - Wartono, Wartono; Giyanto, Giyanto; Mutaqin, Kikin H. (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Bacterial leaf blight control in rice (Oryza sativa Lin.) using bactericide is prohibitive, due to its high cost and its negative effect on the environment. Biocontrol when avaible, therefore is the best alternative solution. Bacillus subtilis is a perspective of biocontrol agent to control several plant diseases, because of its ability to produce antimicrobial and produce plant growth promoting substances. This research was aimed to examine the effectiveness of B. subtilis spore formulation by way of seed treatments and foliar sprays, using different frequencies and concentrations, to control bacterial leaf blight disease (BLB) on rice, caused by Xanthomonas oryzae pv. oryzae, and to evaluate its function as plant growth promoter. The experiments were conducted at greenhouse and in the field using factorial design. At the greenhouse experiment, seed treatment and foliar spray, using concentration of 2% produced better result in controlling BLB, and better result on promoting rice plant growth. In the field experiment, application at 2 week interval showed better effect on suppressing the the disease and on increasing yield. Applications of the formulation of B. subtilis B12 spore reduced BLB disease by 21% and potentially increased yield up to 50%.